2004
DOI: 10.1161/01.res.0000145728.22878.45
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenic Protein 4 Produced in Endothelial Cells by Oscillatory Shear Stress Induces Monocyte Adhesion by Stimulating Reactive Oxygen Species Production From a Nox1-Based NADPH Oxidase

Abstract: Abstract-Atherosclerosis is an inflammatory disease occurring preferentially in arterial regions exposed to disturbed flow conditions including oscillatory shear stress (OS). OS exposure induces endothelial expression of bone morphogenic protein 4 (BMP4), which in turn may activate intercellular adhesion molecule-1 (ICAM-1) expression and monocyte adhesion. OS is also known to induce monocyte adhesion by producing reactive oxygen species (ROS) from reduced nicotinamide adenine dinucleotide phosphate (NADPH) ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
342
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 348 publications
(364 citation statements)
references
References 35 publications
15
342
2
5
Order By: Relevance
“…We have previously shown that Nox4 is more abundantly expressed than Nox2 in cultured BAEC in response to fluid shear stress [25]. In static cultured endothelial cells obtained from the thoracic aortas of C57BL6, Nox4 mRNA was reported to be far more abundant than Nox1 and Nox2 [68]. To show intracellular O 2 −• production, we used dihydroethidium and 2′,7′-dichlorodihydrofluorescein diacetate to account for Nox4 activity in BAEC [69].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Nox4 is more abundantly expressed than Nox2 in cultured BAEC in response to fluid shear stress [25]. In static cultured endothelial cells obtained from the thoracic aortas of C57BL6, Nox4 mRNA was reported to be far more abundant than Nox1 and Nox2 [68]. To show intracellular O 2 −• production, we used dihydroethidium and 2′,7′-dichlorodihydrofluorescein diacetate to account for Nox4 activity in BAEC [69].…”
Section: Discussionmentioning
confidence: 99%
“…Oscillatory sheer stress results in several-fold induction of Nox1, Nox2 and Nox4 in vascular endothelium (with opposite effects of the anti-atherogenic laminar flow that occurs in straight portions of vessels) [80,81]. Oscillatory sheer stress is associated with induction of bone morphogenic protein 4 (BMP4) [82], which induces Nox1 and p47phox, resulting in an oxidative stress that leads to ICAM-1 expression and monocyte adhesion [81]. Nox1 expression increases ~3-fold following balloon injury and precedes restenosis and atherosclerosis [83].…”
Section: Nox Enzymes and Atherosclerosismentioning
confidence: 99%
“…Importantly, oscillatory shear stress leads to continuous O 2 •− production in a NADPH oxidase-dependent manner (Hwang et al 2003), resulting in nuclear factor-κB (NF-κB)-mediated monocyte adhesion. Recent work has shown that bone morphogenic protein-4 (BMP-4) plays a significant role in the response to oscillatory shear stress by stimulating ROS from NADPH oxidases and regulating the expression of ICAM-1 (Sorescu et al 2004). …”
Section: Endothelial Dysfunctionmentioning
confidence: 99%